Reflecting on the Viability of Twitter as Tool in the Postgraduate Supervision Process - Ferreira, J.T. (Frontiers in Education, 2021)
The role of Twitter as an active academic social media space which could complement the postgraduate training process is speculatively contemplated. Literature relating to the notions of online communities in general, digital doctorateness, and other common social media spaces within academia is reviewed. The platform which Twitter potentially provides within the postgraduate training process is deconstructed systematically according to key role players in this process: supervisor and postgraduate students. Some remarks regarding the suitability of Twitter within an African context follows. Contributions with regards to advantages and challenges of this platform is discussed; finally postulating that Twitter may indeed serve as a valuable and meaningful platform to complement the postgraduate training process.